Community-Based Education in the Digital Age: Challenges and Opportunities - Rakuasa, Heinrich; Hidayatullah, Muh; Ardin Suwandi, Mohamad (Journal of Asian Primary Education (JoAPE), 2024)
Community-based education in the digital age presents both challenges and opportunities in transforming learning environments. This study delves into the significance of active community participation, technological innovations, and collaborative efforts in enhancing the quality and inclusivity of education. Through a mixed-methods approach combining literature review and case studies, the research explores the impact of digital access, multi-stakeholder collaboration, and innovative technologies on community-based education. The findings underscore the importance of continuous evaluation, adaptation, and commitment from all stakeholders to create dynamic and inclusive learning ecosystems. In conclusion, strategic collaboration, technological advancements, and ongoing evaluation are essential for harnessing the full potential of community-based education in the digital era, paving the way for inclusive, participatory, and future-oriented learning environmentsCommunity-based education in the digital age presents both challenges and opportunities in transforming learning environments. This study delves into the significance of active community participation, technological innovations, and collaborative efforts in enhancing the quality and inclusivity of education. Through a mixed-methods approach combining literature review and case studies, the research explores the impact of digital access, multi-stakeholder collaboration, and innovative technologies on community-based education. The findings underscore the importance of continuous evaluation, adaptation, and commitment from all stakeholders to create dynamic and inclusive learning ecosystems. In conclusion, strategic collaboration, technological advancements, and ongoing evaluation are essential for harnessing the full potential of community-based education in the digital era, paving the way for inclusive, participatory, and future-oriented learning environments